The counseling process - Patterson, Lewis E. (Brooks/Cole, 1999)
This concise introduction to the counseling process elaborates a three-stage model of counseling, including disclosure, exploration, and action planning, and describes the counselor skills, attitudes, and knowledge essential to therapeutic change. The text assumes an integrated theoretical position, introducing ideas from a variety of theoretical perspectives and explaining how each might contribute to the counselor's work. Full chapters cover: working with children, working with older adults, crisis intervention, gender and multicultural factors, and professional ethics. The Fifth Edition offers a greater focus on skills, incorporates new case studies, and incorporates material on brief therapy.